(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2025)
The uncontrolled use of digital media also has the potential to cause negative impacts, such as decreased social interaction and delayed language development. This study aims to analyze the influence of digital media on the Indonesian language skills of early childhood. This type of research uses a literature study method. Research data were obtained from scientific articles published in the last 10 years (2014–2024) in nationally and internationally reputable journals. The databases used include Google Scholar. The data were analyzed using thematic content analysis techniques. Research results show that although digital media can be an engaging learning tool, supervision from parents and educators is still necessary to ensure its balanced and effective use. The conclusion of this study emphasizes the importance of regulation in the use of digital media to maximize its benefits and minimize negative impacts on children’s language development